PENGARUH TERAPI MUROTTAL TERHADAP TINGKAT HIPERAKTIF – IMPULSIF PADA ANAK ATTENTION DEFICIT HYPERACTIVE DISORDER (ADHD) - Roshinah, Fithroh Roshinah; Nursaliha, Laila; Amri, Saiful (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The research is aimed at revealing the murottal therapy process given to ADHD children and to find out the effect of the therapy on the hyperactive-impulsive behaviours of the ADHD children. The method employed in this research is Subject Single Research (SSR) method using the A-B-A design. The subjects of the reasearch are the third grade students of a special school. The data were collected through observations. The research findings show that the murottal therapy cann reduce the hyperactivity and impulsiveness level among the ADHD children. Such a theraphy positively affects the calmness condition of the ADHD children.